Certainty and severity of sanctions in classical and behavioral models of deterrence: A survey - Horst Entorf (Institute for the Study of Labor (IZA), 2012)
This survey summarizes the classical fundamentals of modern deterrence theory, covers major theoretical and empirical findings on the impact of certainty and severity of punishment (and the interplay thereof) as well as underlying methodological problems, gives an overview of limitations and extensions motivated by recent findings of behavioral economics and discusses 'rational' deterrence strategies in subcultural societies.
urn:nbn:de:101:1-201208096346
Keywords: K4; H0; 330; economics of crime; behavioral economics; deterrence; survey; Strafe; Kriminalitätsökonomik; Verhaltensökonomik